2017
DOI: 10.1177/1687814017732309
|View full text |Cite
|
Sign up to set email alerts
|

A tour route planning model for tourism experience utility maximization

Abstract: Tourism experience has great impact on the tourist satisfaction, and therefore, tourists pay more attention to the tourism experience utility of the tour. The present problem is how to plan the tour route to maximize tourism experience utility considering tourists' preference of attraction, time, and cost budgets. The utility function for the tourism experience, consisting of utilities of tourism activities and travel, was proposed. An optimization model for tour route planning was established with the objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In [31], a 3-stage framework targets on satisfying user preferences for visiting selected POI by generating an optimal personalized route. A tour route planning model was proposed [32] targeting to maximize the tourism experience within a specific budget and time frame by satisfying real-time requirements of Web or mobile users. The method avoids tourists to pass through dangerous zones or areas.…”
Section: Related Work For Route Planning Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [31], a 3-stage framework targets on satisfying user preferences for visiting selected POI by generating an optimal personalized route. A tour route planning model was proposed [32] targeting to maximize the tourism experience within a specific budget and time frame by satisfying real-time requirements of Web or mobile users. The method avoids tourists to pass through dangerous zones or areas.…”
Section: Related Work For Route Planning Modelingmentioning
confidence: 99%
“…Maximization of the tourism experience utility within the tour time and cost budget [32] Mixed 0-1 mixed integer linear programming model…”
Section: Minimum Cost Hamiltonian Cycle Algorithmmentioning
confidence: 99%
“…Therefore, the tourists planning model is used to build high-quality tourist routes. Tour Route Planning Problem (TRPP) is used to maximize tourism experience and build high-quality tourist routes [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The solved TTDP provided an optimal route for the tourist trip design plan (TTDP) in transport vehicles (Yu et al 2014). Wu et al (2017) presented a tour route planning problem (TRPP) solution using a greedy construction procedure for creating a route planning model that maximized the tourism experience utility, considering tourists' preferences in terms of attraction, traveling time, and traveling cost. Tourism visits were time-constrained from 8:30 a.m. until 4:40 p.m. and limited to 200 yuan per day.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the problem solving showed that suitability of attractions, degree of interest, tourism time, and tourism cost considerably influenced the tour route plan. However, traffic significantly impacted traveling time on the route (Wu et al 2017). Similarly, Yan et al (2014) developed a tour route to optimize satisfaction and minimize route distance.…”
Section: Literature Reviewmentioning
confidence: 99%